The Diagnostic Yield of the Multidisciplinary Discussion in Patients With COVID-19 Pneumonia - Calabrese, Fiorella; Pezzuto, Federica; Giraudo, Chiara; Vedovelli, Luca; Fortarezza, Francesco; Del Vecchio, Claudia; Lunardi, Francesca; Fraia, Anna Sara; Cocconcelli, Elisabetta; Vuljan, Stefania Edith; Gregori, Dario; Crisanti, Andrea; et al. (Frontiers in Medicine, 2021)
Purpose: The hypothesis of the study was that a multidisciplinary approach involving experienced specialists in diffuse parenchymal lung disease might improve the diagnosis of patients with COVID-19 pneumonia. Methods: Two pulmonologists, two radiologists, and two pathologists reviewed 27 patients affected by severe COVID-19 pneumonia as the main diagnosis made by non-pulmonologists. To evaluate whether the contribution of specialists, individually and/or in combination, might modify the original diagnosis, a three-step virtual process was planned. The whole lung examination was considered the gold standard for the final diagnosis. The probability of a correct diagnosis was calculated using a model based on generalized estimating equations. The effectiveness of a multidisciplinary diagnosis was obtained by comparing diagnoses made by experienced pulmonologists with those made by non-pulmonologists. Results: In 19% of cases, the diagnosis of COVID-19-related death was mainly incorrect. The probability of a correct diagnosis increased strikingly from an undedicated clinician to an expert specialist. Every single specialist made significantly more correct diagnoses than any non-pulmonologist. The highest level of accuracy was achieved by the combination of 3 expert specialists (p = 0.0003). Conclusion: The dynamic interaction between expert specialists may significantly improve the diagnostic confidence and management of patients with COVID-19 pneumonia.